Assessing the Psychological Impact of Oral Potentially Malignant Disorders Among Patients: Psychological Impact of Oral Potentially Malignant Disorders - Ahmed, Syeda Zehra; Kumar, Santosh; Akhlaq , Humaira; Anwar, Junaid; Lodhi, Mehar; Siddiqui, Dua (Pakistan Journal of Health Sciences, 2025)
Although potential exists for patient-reported outcome measures to assess disease impact, Quality of life evaluation is not widely used in clinical settings. Limited literature exists on the patients’ life quality with oral potentially malignant diseases. Objectives: To evaluate how Oral Potentially Malignant Disorders (OPMDs) affect different realms of quality-of-life QoL, potentially shedding light on variations in QoL depending on the seriousness of the disease. Methods: This cross-sectional study included 70 patients through convenience sampling with potentially malignant disorders: 20 Oral sub mucous fibrosis, 20 Oral lichen planus, 20 Leukoplakia and 5 Actinic keratosis and 5 Erythroplakia. All participants were recruited from Abbasi Shaheed Hospital and Ziauddin University Hospital. The diagnosis of OPMD was made through clinical examination and confirmed by histopathological assessment conducted by oral surgeons. Informed written consent was obtained from all participants, and the SF-12v2 health survey was used for assessment. Results: The oral potentially malignant disorder showed highest occurrence in females than in males in oral submucous fibrosis, leukoplakia and oral lichen planus. The OPMD patients reported impairements in emotional well being and experienced significant pain and functional limitations (p <0.05). Conclusions: The assessment of oral premalignant diseased patients provides valuable insights and understanding of impact of these conditions on their lives. Therefore, this study suggest that OPMD QoL should be routinely checked to enhance patients’ wellbeing and quality of life.